Post-publication careers: lockdown to limelight - Michalea King (Nature Portfolio, 2021)
Media attention to an article on Greenland’s dynamic ice loss provided a Comms Earth author with a way out of pandemic isolation, a broader perspective of her work, and a heavy responsibility to communicate accurately. She found the experience time-consuming, but rewarding.